The rape of Lucretia [opera in two acts] - Britten, Benjamin 1913-1976 (Opus Arte, 2013)
David McVicar's acclaimed production of Benjamin Britten's chamber opera, recorded live during its premiere run at the Aldeburgh Festival in 2001